Patient perspectives on interprofessional collaboration between healthcare professionals during hospitalization: a qualitative systematic review protocol. (August 2017) - Didier, Amélia; Campbell, Joan; Franco, Loris; Serex, Magali; Staffoni-Donadini, Liliana; Gachoud, David; Zumstein-Shaha, Maya
Abstract : Review question/objective: : The objective of this qualitative systematic review is to examine the available evidence on interprofessional collaboration from the patients' perspectives, specifically on: i) interprofessional collaboration in adult or pediatric wards during hospitalization; ii) the influence of interprofessional collaboration on the patient's care, safety and well-being in adult or pediatric wards during hospitalization; and (iii) the patient's role in the interprofessional collaboration process in adult or pediatric wards during hospitalization.